Disparities in parenting criteria: an exploration of the issues, focusing on adoption and embryo donation. Issue 3 (1st June 2002) - Widdows, H; MacCallum, F
Abstract : This paper examines the consistency of parent selection procedures, focusing on adoption and embryo donation. It outlines the current methods of selection and their disparities, and considers reasons for these disparities; namely, the intentionality of the parents, the gestational experience, and the technological imperative. This discussion is followed by an analysis of the ethical validity of these reasons, in terms of their consistency and how well they meet standards of equity and justice. The paper concludes that current approaches to parent selection are unsystematic and inadequate, and discusses the implications of this assessment.